Selection of Protocols to Cryopreserve Mesenchymal Stromal Cells in Suspension and Alginate Microspheres by Studying Their Osmotic Responses in 1M DMSO - Tarusin, Dmitriy N.; Kireyev, Vitaliy A.; Kovalenko, Svetlana Ye.; Kovalenko, Igor F.; Rozanov, Leonid F.; Petrenko, Aleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2016)
We studied the osmotic reaction of mesenchymal stromal cells (MSCs) in suspension and alginate microspheres (AMSs) during their exposure to 1 M solution of DMSO and their viability after cryopreservation with different cooling rates. Numerical modeling allowed to find the permeability coefficient of MSCs membrane for water and DMSO molecules and a change in cell volume at different cooling rates. The cooling rates of 0.5 to 1 deg/min down to –40°C have been shown to result in a substantial dehydration of the cells. The osmotic reaction of MSCs in AMSs was slower than of cells in a suspension, and resulted in a reduced post-thaw viability if cooling rate was 1 deg/min. If the rate was 10 deg/min the cells were not sufficiently dehydrated, highly suggesting a probable intracellular crystallization. Indeed, if the viability of MSCs in the suspension and AMSs after cryopreservation with 1 M DMSO at a cooling rate of 0.5 and 1 deg/min was as much as 75%, the cryopreservation with cooling rates of 10 and 20 deg/min, resulted in the death of about 80% of the cells. Theoretical calculations and experimental studies have shown that to achieve the high levels of viability of MSCs in AMSs the cryopreservation should be implemented with lower cooling rates than for the cells in suspension. Probl Cryobiol Cryomed 2016; 26(2):133-144.